Conceptualising the Commercial Determinants of Health Using a Power Lens: A Review and Synthesis of Existing Frameworks - Benjamin Wood; Phillip Baker; Gary Sacks (Kerman University of Medical Sciences, 2022)
BackgroundThere is increasing recognition that power imbalances that favour corporations, especially those active in unhealthy commodity industries, over other actors are central to the ways in which corporations influence population health. However, existing frameworks for analysing corporate strategies and practices that impact on health do not incorporate concepts of power in consistent ways. This paper aimed to review the ways in which corporate power has been incorporated into such frameworks, and to propose a revised framing of the commercial determinants of health(CDoH) that makes concepts of power explicit. MethodsWe conducted a narrative review of frameworks that identify corporate strategies and practices and explain how these influence population health. Content analysis was conducted to identify explicit references to different qualities of power - its origins, nature, and manifestations. ResultsTwenty-two frameworks were identified, five of which used theories of power. A wide range of contexts that shape, and are shaped by corporate power were discussed, as were a diversity of corporate, social and ecological outcomes. A variety of material and ideational sources of power was also covered. We proposed an integrated 'Corporate Power and Health' framework to inform analysis of the CDoH, organised around key questions on power set out by Foucault. The proposed framework draws from a number of well-established corporate power theories and synthesises key features of existing CDoH frameworks. ConclusionPublic health advocates, researchers and policy-makers would likely be better placed to understand and address the CDoH by engaging with theories of power to a greater extent, and by explicitly incorporating concepts of corporate power in analyses of how the deployment of corporate strategies and practices influence population health.